Cardioprotective Effect of Garlic Juice on the Isolated Rat Heart in Ischemia- Reperfusion - D Shackebaei; S Ghazvineh; A Godini; A Pilehvarian; S Reshadat (Institue of Medicinal Plants, ACECR, 2010)
Background: It has been reported that the chronic oral administration of garlic homogenate protected the rat heart from in vitro ischemic reperfusion injury. However, the biological effects of garlic juice on the heart are expected to be different from oral administration of it. Objective: the present study was designed to investigate the effect of garlic juice on the isolated rat heart in ischemia- reperfusion. Methods: Rat isolated, perfused hearts were subjected to 30 min baseline measurement followed by 40 min normothermic global ischemia and 45 min reperfusion. Garlic juice (0.01 mg/ml) was added to the perfusion solution 20 min before ischemia in the test 1 and 5 min before and 10 min after ischemia in test 2. Different cardiac variables including left ventricular developed pressure (LVDP), heart rate (HR) and coronary flow (CF) were measured. Rate pressure product (RPP) was calculated, and released lactate dehydrogenase (LDH) enzyme in effluent was measured in reperfusion. Results: Garlic juice significantly increased CF before ischemia in both test groups. The released LDH enzyme at the first minute and the recovery of RPP and LVDP on the 45th minute of reperfusion were significantly better in the test group 2 in comparison to the control. Conclusion: The result of the present study shows that garlic juice has a vasodilator activity and protects the isolated ischemic rat heart when it was administrated in reperfusion. It is probably mediated by antioxidant activity of allicin as a principal bioactive compound of garlic juice.